PENGARUH IKLIM ORGANISASI DAN BUDAYA KERJA TERHADAP SEMANGAT KERJA SERTA IMPLIKASINYA TERHADAP PRODUKTIVITAS GURU SDIT BINA ILMI PALEMBANG - Tri - Sinarti; Nisa' Ulul Mafra; Santi - Puspita (JEMBATAN, 2021)
This study aims to determine the direct and indirect effect of organizational climate and work culture variables on work productivity through morale as a mediating variable. The sample in this study were all teachers of the Integrated Islamic Elementary School (SDIT) Bina Ilmi Palembang, totaling 100 people. The sampling technique was saturated sample (census). Data collection was carried out by distributing questionnaires to respondents. The method used is quantitative methods, to look for patterns of relationships and / or patterns of influence between independent and dependent variables. The model in this research is the Path Analysis Model. The path analysis model when translated into a regression equation is two regression equations combined into one research model. Based on the t test, it shows the results of organizational climate have a negative and insignificant direct effect on work productivity. Meanwhile, work culture has a positive and significant direct effect on work productivity. Organizational climate and work culture have a positive and significant indirect effect on work productivity. For the indirect effect, organizational climate and work spirit on work productivity through work spirit shows that the total effect is greater, meaning thatspirit acts as a mediating variable for organizational climate and work culture on teacher productivity.